2015
DOI: 10.1007/s12020-015-0660-4
|View full text |Cite
|
Sign up to set email alerts
|

Value of post-therapeutic 131I scintigraphy in stimulated serum thyroglobulin-negative patients with metastatic differentiated thyroid carcinoma

Abstract: Metastatic differentiated thyroid carcinoma (DTC) with positive (131)I scintigraphy, but negative stimulated Tg (sTg) is relatively rare in clinical practice. The clinical characteristics of these patients were analyzed in the current study. A total of 3367 consecutive histologically proven DTC patients were analyzed retrospectively from January 2007 to June 2013. Tg negativity was defined as a sTg level of <2 ng/mL without positive anti-Tg antibody (TgAb level of <100 IU/mL) under thyroid-stimulating hormone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…For this reason, it is necessary to perform imaging screening at the early stage of TT and conduct research and investigation for TT [ 3 , 4 ]. CEUS, as an important clinical imaging diagnostic method, has been promoted and expanded because of its meticulous imaging observation of TT and clear tumor nodules [ 5 , 6 ]. Contrast-enhanced ultrasonography stands out in the judgment of TC tumors, but the traditional ultrasound examination of thyroid nodules has a large overlap in the image of BAM thyroid nodules, which makes the clinical practice of ultrasound diagnosis of BAM thyroid nodules facing major challenges [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, it is necessary to perform imaging screening at the early stage of TT and conduct research and investigation for TT [ 3 , 4 ]. CEUS, as an important clinical imaging diagnostic method, has been promoted and expanded because of its meticulous imaging observation of TT and clear tumor nodules [ 5 , 6 ]. Contrast-enhanced ultrasonography stands out in the judgment of TC tumors, but the traditional ultrasound examination of thyroid nodules has a large overlap in the image of BAM thyroid nodules, which makes the clinical practice of ultrasound diagnosis of BAM thyroid nodules facing major challenges [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A negative serum Tg and positive WBS has been reported in a small, but significant number of cases [4][5][6][14][15][16]. Falsenegative serum Tg occurred in patients with small PTC with cervical or mediastinal lymph node metastases, in follicular thyroid cancer (FTC) patients with bone metastases, and in 8.5% of DTC patients with metastases [4].…”
Section: Discussionmentioning
confidence: 99%
“…After 1-year follow-up, four out of 42 patients with initially a positive serum Tg and positive WBS showed a negative Tg and positive WBS, suggesting that diagnostic WBS is a valuable tool in addition to the Tg level [15]. Shen et al [16] reported that 71 (2.1%) among a total of 3,367 DTC patients had a negative serum Tg and positive post-therapeutic WBS. Of these 71 patients, two (2.8%) patients had bone metastasis, 11 (15.5%) had lung metastasis, and 59 (83.1%) had lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%